Idiom Bahasa Mandailing di Kenagarian Simpang Tonang Kecamatan Dua Koto Kabupaten Pasaman - Sumanti, Pepi; Ermanto, Ermanto; Nst., Bakhtaruddin (Universitas Negeri Padang, 2012)
There are three the purpose of writing article: (1) describes the form of idioms and the dominant form used of community at Kenagarian Simpang Tonang Kecamatan Dua Koto Kabupaten Pasaman, (2) describes the meaning of the idiom that are used by society at Kenagarian Simpang Tonang Kecamatan Dua Koto Kabupaten Pasaman, (3) describes function of idiom and the function that dominant idiom are used by society at Kenagarian Simpang Tonang Kecamatan Dua Koto Kabupaten Pasaman. Therefore, types of research was choosed descriptive qualitative research method. Result of this research are found 75 idiom that is full idiom and idiom partly idioms are also grouped by such constituent words likes constituent words such as, idioms with parts of body, idioms with color, idiom as natural objects, idiom with the name of the beast, idioms with parts of plants, and idioms with the word number. Idiom works to (1) to satirize, (2) praise, (3) express anger, (4) expressing joy or affection, and (5) express sadness.